2016
DOI: 10.1038/srep24174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of 2013 Sudden Stratospheric Warming event and its impact on cold weather over Eurasia: Role of planetary wave reflection

Abstract: In the present study, we investigate the impact of stratospheric planetary wave reflection on tropospheric weather over Central Eurasia during the 2013 Sudden Stratospheric Warming (SSW) event. We analyze EP fluxes and Plumb wave activity fluxes to study the two and three dimensional aspects of wave propagation, respectively. The 2013 SSW event is excited by the combined influence of wavenumber 1 (WN1) and wavenumber 2 (WN2) planetary waves, which makes the event an unusual one and seems to have significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…The fluctuations of the easterlies observed in the reanalysis after the reversal are not captured by any ensemble members. Karpechko et al (2018) showed that most ensemble members underestimated the eddy heat flux at 100 hPa, which is used to characterize the upward planetary wave propagation from the troposphere to the stratosphere since it is proportional to the vertical group velocity of a planetary wave and to the vertical component of the Eliassen-Palm flux (Newman et al, 2001). With the reduction of the lead time, the prediction skill increases rapidly, and all ensemble members of the forecast initialized on 5 February capture the onset of the SSW (Fig.…”
Section: Stratospheric Forecastsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluctuations of the easterlies observed in the reanalysis after the reversal are not captured by any ensemble members. Karpechko et al (2018) showed that most ensemble members underestimated the eddy heat flux at 100 hPa, which is used to characterize the upward planetary wave propagation from the troposphere to the stratosphere since it is proportional to the vertical group velocity of a planetary wave and to the vertical component of the Eliassen-Palm flux (Newman et al, 2001). With the reduction of the lead time, the prediction skill increases rapidly, and all ensemble members of the forecast initialized on 5 February capture the onset of the SSW (Fig.…”
Section: Stratospheric Forecastsmentioning
confidence: 99%
“…During the last decade the events occurred in 2013, 2018 and 2019. The 2013 and 2018 events were followed by cold and snowy weather in Europe (Nath et al, 2016; Published by Copernicus Publications on behalf of the European Geosciences Union. I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pacific blocking also explains why the stratospheric polar vortex was shifted over Eurasia prior to the SSW of January, 2013. Nath et al (2016) found that upward propagating wave packets from North Pacific and Siberian Tundra were possibly responsible for the wave-2 vortex-splitting event. Further they supposed that the wave packets are reflected back downward to central Eurasia due to the strong negative wind shear of the upper stratospheric polar vortex.…”
Section: The Major Ssw Of January 6 2013mentioning
confidence: 97%
“…Stratospheric warming events are known to be forced by upward propagating Rossby and gravity waves from the upper troposphere. In a number of recent studies (e.g., Martius et al 2009;Nath et al 2016;Harada and Hirooka 2017), the two-way coupling between the troposphere and the stratosphere has been demonstrated. The effects of stratospheric dynamics on tropospheric weather were not much acknowledged until late 1990s (see Kidston et al 2015 for a recent review).…”
Section: Introductionmentioning
confidence: 99%